Comparación entre un diseño realizado mediante un análisis estático y uno dinámico de historia en el tiempo para una estructura de mezanine sometida a vibraciones - Monge-Ruiz, Benyamin Franklin (Instituto Tecnológico de Costa Rica, 2017)
This work consists of an evaluation of the vibrations in a mezzanine structure designed by a static analysis, using a live load using instead of the real live load exerted by a machine on the structure. A design of the same structure but through a dynamic analysis time-history, using a live load is applied periodically with the real frequency that the machine exerts on the mezzanine. A model is created in the software SAP2000 that describes in a more real way this phenomenon. The structural design was performed, and fatigue compliance was checked on the elements. The vibration compliance was reviewed for both structures according to the regulations applied. It was identified as the main limitation for the history-time analysis the obtaining of the function that describes the periodicity and magnitude of the load exerted by the machine on the structure. The cost of the structure designed by static method is about 200% more than that designed by the dynamic method of time-history.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Vibración; Diseño; Estructuras; Maquinaria; Construcción